Raspberry Pi Essential Training. - Niemann-Ross, Mark (linkedin.com, 2022)
Learn the basic vocabulary of Raspberry Pi, as well as how to plug in peripherals and perform basic computing tasks. You can also gain an understanding of the GPIO and Pico boards.